2018
DOI: 10.1158/0008-5472.can-17-0028
|View full text |Cite
|
Sign up to set email alerts
|

hPCL3s Promotes Hepatocellular Carcinoma Metastasis by Activating β-Catenin Signaling

Abstract: Two isoforms of human Polycomb-like protein 3 (hPCL3) have been reported as components of the nuclear Polycomb repressive complex 2 (PRC2), with the short isoform (hPCL3s) showing a dominant cytoplasmic localization. The function of cytoplasmic hPCL3s has, however, not been addressed. In this study, we report that hPCL3s is upregulated in clinical hepatocellular carcinoma (HCC) samples and its expression correlated with HCC clinical features. hPCL3s positively regulated the migration, invasion, and metastasis … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 25 publications
(28 reference statements)
1
37
0
Order By: Relevance
“…In liver cancer, P53 deletion and the Kras G12D activating mutation are very common. Based on this, we established a model of spontaneous HCC (Alb‐Cre; P53 fl/fl ; Kras G12D ) by crossing Alb‐Cre mice with mice expressing LSL‐Kras G12D and P53 fl/fl . Simply, the Cre enzyme expressed by the mice is regulated by the Alb gene promoter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In liver cancer, P53 deletion and the Kras G12D activating mutation are very common. Based on this, we established a model of spontaneous HCC (Alb‐Cre; P53 fl/fl ; Kras G12D ) by crossing Alb‐Cre mice with mice expressing LSL‐Kras G12D and P53 fl/fl . Simply, the Cre enzyme expressed by the mice is regulated by the Alb gene promoter.…”
Section: Resultsmentioning
confidence: 99%
“…These genes were cloned into the p23/pLKO.1 vectors or for transient (using the Lipofectamine 2000 according to the manufacturer's instructions; Thermo Fisher Scientific, Waltham, MA, USA) or stable expression in 7404 or Huh‐7 cells. The lentivirus was used to produce the stable transformants.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, recruitment of PRC2 to DNA regions of target genes to catalyze the methylation of lysine 27 on histone 3 (H3K27me3), are essential for controlling the developmental gene expression and maintaining cell specification (Kouznetsova et al, 2019). Aberrant expression of PHF19 has been implicated in regulating the pathogenesis and progression of a wide range of cancers, including melanoma (Ghislin et al, 2012), hepatocellular carcinoma (Xu et al, 2015;Cai et al, 2018), glioma (Lu et al, 2018), glioblastoma (Deng et al, 2018), multiple myeloma (Ren et al, 2019). In our previous publication, we have found that patients with higher expression of PHF19 are associated with shorter progressionfree survival (PFS) than that with lower PHF19 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Membranes were blocked with 5% milk at room temperature for 1 h, and probed with primary and secondary antibodies. The immunoreactive protein bands were visualized using an Enhanced Chemiluminescence kit (Pierce; Thermo Fisher Scientific, Inc. Staining was assessed using the H-score method (21), according to the following equation: H-score=Σ(i x Pi). The staining intensity i) of the tumour cells was graded from 0-3, and Pi was the percentage of stained cells at each staining intensity.…”
Section: Hsp90 Interacts With Hmgcr and Promotes The Progression Of Hmentioning
confidence: 99%